2021
DOI: 10.1007/s11029-021-09966-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of the “Separated Anisotropy” Concept in the Theory of Gradient Anisotropic Elasticity

Abstract: A variation model of the gradient anisotropic elasticity theory is constructed. Its distinctive feature is the fact that the density of potential energy, along with symmetric fourth-and sixth-rank stiffness tensors, also contains a nonsymmetric fifth-rank stiffness tensor. Accordingly, the stresses in it also depend on the curvatures and the couple stresses depend on distortions. The Euler equations are three fourth-order equilibrium equations. The spectrum of boundary-value problems is determined by six pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In [3][4][5][6][7], it is shown that for the extensive class of elasticity models, including those regarding gradient elasticity, additional symmetry conditions from classical elasticity models must be met. Otherwise, models intended to simulate a deformable, defect-free medium become erroneous because the condition of the continuity of distortions, i.e., the condition of the absence of a field of defects, is not satisfied.…”
Section: Description Of Articles [12]mentioning
confidence: 99%
See 1 more Smart Citation
“…In [3][4][5][6][7], it is shown that for the extensive class of elasticity models, including those regarding gradient elasticity, additional symmetry conditions from classical elasticity models must be met. Otherwise, models intended to simulate a deformable, defect-free medium become erroneous because the condition of the continuity of distortions, i.e., the condition of the absence of a field of defects, is not satisfied.…”
Section: Description Of Articles [12]mentioning
confidence: 99%
“…Therefore, it also extends to non-gradient models of anisotropic media, for which the general structure of elastic modulus tensors is very complex. These issues were partly considered in [4,6]. The same papers discuss the issues of symmetry in the structure of elastic modulus tensors related to the potentiality of the strain energy density and the issues of the inheritance of the symmetrical anisotropy properties from the classical theory in a gradient anisotropic medium.…”
Section: Description Of Articles [12]mentioning
confidence: 99%